2010
DOI: 10.1007/s00421-010-1688-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between oxygenation and myoelectric activity in the forearm and shoulder muscles of males and females

Abstract: The aim was to investigate the relationship between oxygen saturation (StO(2)%) measured with near-infrared spectroscopy (NIRS) and myoelectric activity (root mean square, RMS) for the extensor carpi radialis (ECR) and trapezius muscles. In addition, gender differences were examined for submaximal (10-70% MVC) and sustained (10% MVC for 5 min) isometric contractions. Thirteen males and 15 females participated. Changes in StO(2)% (∆StO(2)%) and RMS, expressed as percentages of maximum, were calculated for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
0
26
0
1
Order By: Relevance
“…The magnitudes of changes over contraction force are discussed in detail in our previous publication (Elcadi et al 2011). While some studies report interday test-retest reliability for a single contraction (Kell et al 2004;Maikala and Bhambhani 2009), we found one recently published study of particular relevance that examined forearm oxygenation responses during handgrip exercise at various intensities ranging from 20% MVC to maximal adjusted in 10% MVC increments (Celie et al 2011).…”
Section: Isometric Contractions Datamentioning
confidence: 95%
See 4 more Smart Citations
“…The magnitudes of changes over contraction force are discussed in detail in our previous publication (Elcadi et al 2011). While some studies report interday test-retest reliability for a single contraction (Kell et al 2004;Maikala and Bhambhani 2009), we found one recently published study of particular relevance that examined forearm oxygenation responses during handgrip exercise at various intensities ranging from 20% MVC to maximal adjusted in 10% MVC increments (Celie et al 2011).…”
Section: Isometric Contractions Datamentioning
confidence: 95%
“…Of note, these same landmarks were used in a number of our previous studies (e.g. Elcadi et al 2011) to represent the ECR, however, we cannot be absolutely sure that the ECR exclusively was the muscle that measurements were obtained from at this site. The site on the TD was one-third the distance (in a lateral direction) between C7 and the acromion process of the scapula.…”
Section: Experimental Set Up and Protocolmentioning
confidence: 98%
See 3 more Smart Citations